2011
DOI: 10.5761/atcs.oa.09.01507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Device for the Intraoperative Assessment of Coronary Artery Bypasses Grafting

Abstract: Purpose: The aim of this study was to evaluate a new flow analyze device that can intraoperatively measure compliance and resistance of coronary artery bypass grafting (CABG) by the parameter identification method. Methods: Subjects were 95 patients who underwent CABG. Angiography soon after surgery confirmed patency in 90 grafts and graft failure in 5 grafts. Variables of Aortic pressure and the graft flow were entered into this new device that includes a mathematical coronary circulation model to extrapolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In this milieu therefore, when anaortic total arterial bypass, places 'all eggs in limited baskets', it is very important that some form of intra operative assessment of grafts, preferably using both morphological and functional imaging techniques, 16 must be resorted to in order to pick and remedy inadvertent errors, and thereby avoid potentially disastrous consequences. Bonatti et al showed that three out of 23 patients needed graft revision based on intra operative angiography.…”
Section: Anaortic Graftingmentioning
confidence: 99%
“…In this milieu therefore, when anaortic total arterial bypass, places 'all eggs in limited baskets', it is very important that some form of intra operative assessment of grafts, preferably using both morphological and functional imaging techniques, 16 must be resorted to in order to pick and remedy inadvertent errors, and thereby avoid potentially disastrous consequences. Bonatti et al showed that three out of 23 patients needed graft revision based on intra operative angiography.…”
Section: Anaortic Graftingmentioning
confidence: 99%